SISTEM PAKAR DENGAN METODE FORWARD CHAINING UNTUK MENENTUKAN PEMBAGIAN WARISAN MENURUT HUKUM ISLAM MENGGUNAKAN ALGORITMA BEST FIRST SEARCH - Anton Setiawan Honggowibowo; Yuliani Indrianingsih; Anis Syaul Umami (Compiler, 2017)
In Islamic law, the division of inheritance according to the provisions of Islamic rule is an obligation. It is encouraged to immediately  distribute inheritance without delaying. The manual process of dividing inheritance according to islamic law requires a lot of time and expertise, which is not everyone capable of. So there is a need for providing an expert system for dividing inheritance according to Islamic law that can help people to hasten the implementation of Islamic sharia in distributing inheritance. This expert system is a web-based system. Transformation of expertise knowledge in this expert system uses forward chaining method with best first search algorithm. The result of the consultation on this expert systemconsist of the complete profile data of the deceased, the blocked-heirs, the portion for each heir and the portion of the inheritance for each heir.